Faktor yang Memengaruhi Kinerja Verifikasi Dokter Verifikator Internal Medis dalam Proses Klaim Pasien Jaminan Kesehatan Nasional di Rumah Sakit Cipto Mangunkusumo - Tarigan, Immanuel Natanael; Oktamianti, Puput; Darmawan, Ede Surya (UI Scholars Hub, 2024)
Since the implementation of the National Health Insurance, hospitals must be able to manage JKN claims properly. One way to properly manage the situation is by employing a medical internal verification doctor. This study aims to determine the factors that influence the performance of medical internal verification doctor based on the percentage of claim eligibility that has been verified. The research was conducted using a case study method with a qualitative and quantitative approach. The study was conducted on 16 medical internal verification doctors using questionnaires and in-depth interviews. The results of the study found that the performance of medical internal verification doctors in January-June 2022 was 81.45%, lower than other hospital owned by the ministry of health (85-94%). This study also found that the factors related to the verification performance of medical internal verification doctors were demographic in the form of years of service as medical internal verification doctors and other workloads, knowledge, job satisfaction in general, satisfaction with salary, benefits and rewards for work, satisfaction with the nature of work, as well as satisfaction with the operational situation of work and colleagues. Other factors in medical internal verification doctors verification performance is organizational support, such as standard operating procedures, training and education opportunities and opportunities for communication with external parties. Other factors related to the verification performance of VIM doctors are the passion as a medical internal verification doctor, tasks assignment, feedback on performance and criteria or standards for becoming a medical internal verification doctors.